Hypertension Guidelines (NICE-BIHS Guideline - 2011, ESH/ESC Guideline - 2013, JNC Guideline - 2014) - Editor, The (BIRDEM Medical Journal, 2016)
Abstract not available Birdem Med J 2015; 5(1) Supplement: 1-11